Cryptococcus extracellular vesicles properties and their use as vaccine platforms. Issue 10 (2nd August 2021) - Rizzo, Juliana; Wong, Sarah Sze Wah; Gazi, Anastasia D.; Moyrand, Frédérique; Chaze, Thibault; Commere, Pierre‐Henri; Novault, Sophie; Matondo, Mariette; Péhau‐Arnaudet, Gérard; Reis, Flavia C. G.; Vos, Matthijn; Alves, Lysangela R.; et al.
Abstract: Whereas extracellular vesicle (EV) research has become commonplace in different biomedical fields, this field of research is still in its infancy in mycology. Here we provide a robust set of data regarding the structural and compositional aspects of EVs isolated from the fungal pathogenic species Cryptococcus neoformans, C. deneoformans and C. deuterogattii . Using cutting‐edge methodological approaches including cryogenic electron microscopy and cryogenic electron tomography, proteomics, and flow cytometry, we revisited cryptococcal EV features and suggest a new EV structural model, in which the vesicular lipid bilayer is covered by mannoprotein‐based fibrillar decoration, bearing the capsule polysaccharide as its outer layer. About 10% of the EV population is devoid of fibrillar decoration, adding another aspect to EV diversity. By analysing EV protein cargo from the three species, we characterized the typical Cryptococcus EV proteome. It contains several membrane‐bound protein families, including some Tsh proteins bearing a SUR7/PalI motif. The presence of known protective antigens on the surface of Cryptococcus EVs, resembling the morphology of encapsulated virus structures, suggested their potential as a vaccine. Indeed, mice immunized with EVs obtained from an acapsular C. neoformans mutant strain rendered a strong antibody response in mice and significantly prolonged their survival upon C. neoformans infection.